Differentiation of pituitary macroadenoma and craniopharyngioma in adult Patients: MRI findings - Radchauppanone, Panupong; Oranratanachai, Kanokporn; Angkurawaranon, Salita; Unsrisong, Kittisak; Suwansirikul, Songkiet (Biomedical Sciences and Clinical Medicine, 2016)
Objective To compare the MRI findings between pituitary macroadenoma and craniopharyngioma. Methods This retrospective study was conducted at our university Hospital. Patient data between January 2006 to June 2014 were reviewed. Pathological proof of pituitary macroadenoma 61 patients and other 10 patients of craniopharyngioma were included in the study. The patient data were categorized into gender and age. MRI findings analysed the tumor size, shape, component, adjacent brain edema, cavernous sinus invasion, sellar widening, presence of posterior T1-weighted bright spot, presence of normal pituitary gland, signal intensity of solid/cystic components on T1 and T2-weighted images and pattern of enhancement. Results A snowman or ovoid shape with solid component, presence of sellar widening and posterior T1 bright spot were suggestive of pituitary macroadenoma (p<0.05). A lobulated shape with cystic component, presence of adjacent brain edema, epicenter of the tumor in suprasellar region which could be separable from the normal pituitary gland and presence of rim enhancement were suggestive of craniopharyngioma (p<0.05). Conclusion MRI findings were helpful to distinguish between pituitary macroadenoma and craniopharyngioma by using tumor shape, component, sellar widening, presence of posterior T1 bright spot, adjacent brain edema, epicenter of the tumor in suprasellar region which could be separable from the normal pituitary gland and presence of rim enhancement.